Politics and Implementation Challenges in Indonesia's Curriculum Policy Transformation - Alhamuddin Alhamuddin; Andi Murniati (AL-ISHLAH: Jurnal Pendidikan, 2025)
Curriculum reform in Indonesia is shaped by complex political, social, and economic dynamics. This study investigates how political factors influence curriculum changes, identifies challenges in implementation, and offers recommendations for more effective and inclusive development. A mixed-methods approach was used, combining a literature review of relevant policy documents and previous research with a teacher-focused survey. The survey explored educators’ perspectives on the practical challenges of implementing curriculum reforms. Findings indicate that curriculum change in Indonesia is heavily influenced by political interests, including those of government bodies, political parties, and community leaders. Implementation challenges are pronounced, with disparities in regional infrastructure and educational resources, insufficient teacher readiness, and frequent policy shifts. Moreover, limited public involvement in the curriculum development process contributes to resistance, particularly in areas sensitive to cultural and social norms. The study highlights that without inclusive stakeholder participation and stable policy environments, curriculum reforms risk inefficiency and rejection at the grassroots level. Teachers often lack the support and resources necessary for effective implementation. To address these challenges, curriculum development must prioritize inclusive collaboration, equitable distribution of educational resources, and consistent teacher training. Ongoing evaluation and adaptable policy design are essential to align the curriculum with societal changes while maintaining educational stability.